Clinical and radiographic outcome of pulpotomy using Biodentine, in primary mandibular second molar teeth - Jaziya Z , Dr.; Digesh Balachandran , Dr.; Rita Zarina. A , Dr. (International Journal of Dental Research, 2024)
Aims: The aim of the study was to assess the clinical and radiographical treatment outcome following pulpotomy using Biodentine, in primary mandibular second molar teeth.Settings and Design: Tertiary dental health care setting (Government Dental college Thiruvananthapuram), Prospective studyMethods and Material: A total 27 consecutive patients ranging in age from 4-8 years, satisfying the inclusion and exclusion criteria participated in the study. Pulpotomy procedure was carried out using Biodentine and followed up at 3, 6, 12 month’s intervals. The clinical success criteria in terms of absence of pain, pathologic mobility, swelling, sinus and radiographic success criteria in terms of pathologic root resorption, periapical and furcal radiolucency were noted. Evaluation of the treatment outcomes were based on clinical and radiographic examination. The resulting data were tabulated and statistically analysed.Statistical analysis used: SPSS version 25.0 was used to analyse the dataResults: At the end of the 1-year follow-up, the clinical and radiographic success rates were 92.5% and 88.9%, respectively.Conclusions: Biodentine as a pulpotomy agent has a high successful rate and fulfilled all requirements of an ideal pulpotomy medicament. Hence Biodentine could be routinely used in practice for the treatment of carious primary molars. The excellent outcomes of the present study are truly indicative of Biodentine being a promising pulp repair agent for pulpotomy in clinical practice.